The harder you fall eaudiobook Original heartbreakers series, book 3. - Showalter, Gena (Original Heartbreakers, 2015)
From New York Times bestselling author Gena Showalter comes another scorching Original Heartbreakers tale featuring an aloof bad boy and the rowdy Southern belle who rocks his world. Millionaire video-game creator Lincoln West has a dark and tragic past. The sought-after bachelor lives by a rigid schedule and a single rule-one relationship per year, lasting no more than two months. No exceptions. When he gave up the big city for a small town, he hoped to escape the worst of his memories-until a brash beauty dredges up long-buried emotions. A reformed party girl, Jessie Kay Dillon is determined to walk the straight and narrow. But her love-hate sizzle with West is just too irresistible. They can't be near each other without tearing off their clothes, but the last thing she needs is to be his next two-month dump. Will she become the one exception? Because as any former girl-gone-wild knows: rules are made to be broken. "Emotional, heart-tugging, kept me turning the pages!" -Carly Phillips, New York Times Bestselling Author